2022
DOI: 10.3389/fsurg.2022.905558
|View full text |Cite
|
Sign up to set email alerts
|

Women in Surgery Events Alone do not Change Medical Student Perceptions of Gender Bias and Discrimination in Orthopaedic Surgery

Abstract: AimsThis study investigated the perceptions of medical students regarding the barriers to pursuing a career in trauma and orthopaedics (T&O); and whether these perceptions were altered by attending an event promoting women in T&O.MethodsAn event consisting of presentations and interactive sessions from two female T&O trainees was hosted online. Attendees completed pre and post-event questionnaires. Students were asked about their previous exposure to T&O, perceptions of gender i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This finding is consistent with the literature. There is evidence that early exposure is critical for increasing female medical students’ interest in orthopedic surgery [13]. However, in light of the fact that the difference in percentages of exposure of the two groups to this field during their medical studies was relatively small—80% versus 60%—it can be suggested that the early exposure possibly plays a certain role in the choice of this field, but this role is not significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with the literature. There is evidence that early exposure is critical for increasing female medical students’ interest in orthopedic surgery [13]. However, in light of the fact that the difference in percentages of exposure of the two groups to this field during their medical studies was relatively small—80% versus 60%—it can be suggested that the early exposure possibly plays a certain role in the choice of this field, but this role is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the desire to specialize in orthopedics possibly appears even before the medical studies, thus supporting previous findings. There is evidence that students choosing orthopedics often make this decision prior to medical school [13, 15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown that activities and initiatives to support women in surgery without other institutional support do not change students' perception of gender bias in surgery. 30 Institutional support may include promoting equitable career progression for women surgeons, mitigating gender bias and discrimination in the workplace, and increasing the number of women surgeons across subspecialties. In our study, we found that although USMLE Step 1 and satisfaction with surgery clerkship was significantly associated with both sustained and cultivated paths in surgery, it did not mitigate the sociodemographic disparity in retention of surgical career.…”
Section: Discussionmentioning
confidence: 99%